A Right and Left. - Mecham, William, 1853-1902; Merry, Tom (My University, 1800)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Great Britain -- Politics and government -- 1837-1901 -- Caricatures and cartoons; Hunting